Germline and somatic imprinting in the nonhuman primate highlights species differences in oocyte methylation - Cheong, Clara Y.; Chng, Keefe; Ng, Shilen; Chew, Siew Boom; Chan, Louiza; Ferguson-Smith, Anne C. (Genome Research, 2015)
Genomic imprinting is an epigenetic mechanism resulting in parental allele-specific gene expression. Defects in normal imprinting are found in cancer, assisted reproductive technologies, and several human syndromes. In mouse models, germline-derived DNA methylation is shown to regulate imprinting. Though imprinting is largely conserved between mammals, species- and tissue-specific domains of imprinted expression exist. Using the cynomolgus macaque (Macaca fascicularis) to assess primate-specific imprinting, we present a comprehensive view of tissue-specific imprinted expression and DNA methylation at established imprinted gene clusters. For example, like mouse and unlike human, macaque IGF2R is consistently imprinted, and the PLAGL1, INPP5F transcript variant 2, and PEG3 imprinting control regions are not methylated in the macaque germline but acquire this post-fertilization. Methylome data from human early embryos appear to support this finding. These suggest fundamental differences in imprinting control mechanisms between primate species and rodents at some imprinted domains, with implications for our understanding of the epigenetic programming process in humans and its influence on disease.